(untitled) (Stamford Journal of Pharmaceutical Sciences, 2010)
The pet-ether soluble fraction (PEF), Carbon tetrachloride soluble fraction (CTSF) and Chloroform soluble fraction (CFSF) of the methanolic extract of stem bark of Elaeocarpus serratus were investigated for cytotoxic activity using brine shrimp lethality bioassay .The methanolic extract was also evaluated for possible antioxidant activity using nitric oxide scavenging activity and reducing power assays. In Elaeocarpus serratus, the LC50 value were found to be 14.94, 0.831 & 3.288 μg/mL in pet-ether soluble fraction (PEF), Carbon tetrachloride soluble fraction (CTSF) and Chloroform soluble fraction (CFSF) of the methanolic extract respectively. The extract showed significant antioxidant activity in nitric oxide scavenging activity and reducing power assay. In nitric oxide scavenging activity, the IC50 value of Elaeocarpus serratus extract was 89.325μg/mL while the IC50 value of ascorbic acid was 47.684μg/mL. It was found that scavenging of nitric oxide by the extract was concentration dependent. Key words: Elaeocarpus serratus; Cytotoxicity; Antioxidant; Reducing power. DOI: 10.3329/sjps.v2i2.5829 Stamford Journal of Pharmaceutical Sciences Vol.2(2) 2009: 86-90